2019
DOI: 10.1182/blood-2019-125436
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Effect of the EZH1/2 Dual Inhibitor Valemetostat Against Diffuse Large B-Cell Lymphoma Via Modulation of B-Cell Receptor Signaling and c-Myc Signaling Pathways

Abstract: Enhancer of zeste homolog (EZH) 1 and its close homolog EZH2 are component of polycomb repressive complex 2 (PRC2), and play a partially redundant and crucial role for the maintenance of transcriptional repression by tri-methylating histone H3 lysine 27 (H3K27). Hyper tri-methylation of H3K27 have been associated with lymphoma and myeloma progression, suggesting PRC2 is a therapeutic target for hematological malignancies. We have developed a novel EZH1 and EZH2 dual inhibitor valemetostat (DS-32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A phase 1/2 study is undergoing to evaluate the efficacy of MAK683 in a variety of malignancies, including DLBCL (NCT02900651). Further, the EZH1 and EZH2 dual inhibitor valemetostat (DS-3201b) had antitumor activities in both ABC and GCB DLBCL cells in vitro, which is now under investigation in a phase I trial for advanced NHL including DLBCL [ 135 ].…”
Section: Epigenetic-modifying Drugsmentioning
confidence: 99%
“…A phase 1/2 study is undergoing to evaluate the efficacy of MAK683 in a variety of malignancies, including DLBCL (NCT02900651). Further, the EZH1 and EZH2 dual inhibitor valemetostat (DS-3201b) had antitumor activities in both ABC and GCB DLBCL cells in vitro, which is now under investigation in a phase I trial for advanced NHL including DLBCL [ 135 ].…”
Section: Epigenetic-modifying Drugsmentioning
confidence: 99%
“…EZH2 is the catalytic subunit of polycomb repressive complex 2 (PRC2), which regulates downstream gene expression by trimethylation of lysine 27 in histone H3 (H3K27me3) [1]. Previous studies reported that EZH1/2 inhibitor valemetostat could induce apoptosis in HTLV-1-infected cells, ATL cells, and other cancer cell lines in vitro [2][3][4]. However, there are no data demonstrating that valemetostat could induce apoptosis in vivo when valemetostat is administered in humans.…”
mentioning
confidence: 99%